Graphene / sulfur / silicon multi-component composite material for manufacturing battery electrode, preparation method of graphene / sulfur / silicon multi-component composite material and battery

By loading elemental sulfur and silicon onto the graphene surface to form graphene/sulfur/silicon multi-component materials, the existing battery electrode materials have solved the problems of low lithium storage capacity and serious volume expansion, and the battery performance of high energy storage, high cycle stability and low expansion are achieved.

CN119674018APending Publication Date: 2025-03-21AMPREUS WUXI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411890009.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing lithium-ion battery electrode materials have low lithium storage capacity, small volume density, and poor conductivity of elemental sulfur and silicon, resulting in severe volume expansion during charging and discharging, and uneven distribution of micron-level particles, so they cannot be used as electrode materials alone.

Method used

The co-deposition method is used to load elemental sulfur and elemental silicon onto the surface of graphene, and the energy storage, cycling and rate performance of the battery is improved through the synergistic effect of graphene/sulfur/silicon multi-component materials.

Benefits of technology

High discharge specific capacity and good cycle stability are achieved, silicon expansion problems are avoided, and the actual specific capacity and energy density of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005200422000000011
    Figure HDA0005200422000000011
  • Figure HDA0005200422000000021
    Figure HDA0005200422000000021
Patent Text Reader

Abstract

The invention discloses a graphene / sulfur / silicon multi-component composite material for manufacturing a battery electrode, a preparation method and a battery, and belongs to the technical field of batteries, the graphene / sulfur / silicon multi-component composite material is a multi-component composite material taking graphene as a substrate to load nano sulfur and nano silicon; in the multi-component composite material, nano-silicon is deposited on the surface layer of graphene, and nano-sulfur is uniformly crystallized to the surfaces of nano-silicon particles and among the particles. According to the graphene / sulfur / silicon multi-component composite material and the preparation method thereof, the respective advantages of the composition materials are exerted through a material compounding technology, the defects of a single material are overcome, and the prepared graphene / sulfur / silicon multi-component composite material has the advantages of high charge-discharge capacity, long cycle life, good rate capability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries and relates to a negative electrode material for a battery, and in particular to a graphene / sulfur / silicon multi-component composite material for making battery electrodes, a preparation method, and a battery. Background Art

[0002] In recent years, with the development of science and technology, in order to meet the needs of human beings for high-quality high-tech life, the requirements for lithium-ion batteries used in electric vehicles, energy storage systems, digital, starting power supplies, drones, etc. have become increasingly stringent. Many researchers have invested a lot of energy and financial resources in the research of existing lithium-ion battery electrode materials. Graphene has been widely studied because of its unique electrical, mechanical, and thermal properties. The theoretical specific surface area of ​​graphene is 2600m 2 / g, conductivity up to 8×10 5 S / m, the thickness of the single layer is 0.3354nm. If graphene is used alone as an electrode material for lithium-ion batteries, its lithium storage capacity is low, and its volume density is too small to limit its practical application. The theoretical specific capacity of elemental sulfur is 1680mAh / g, and the theoretical energy density is 2600Wh / kg. The theoretical specific capacity of elemental silicon is 4200mAh / g. Both are abundant in resources, non-toxic and harmless, and are considered to be electrode materials with great application prospects. However, due to the poor conductivity of sulfur and silicon, the volume expansion is severe during charging and discharging, and the micron-level particle size and uneven distribution make it impossible to use them alone as electrode materials. Summary of the invention

[0003] In view of the defects in the prior art, the present invention utilizes nanocomposite material preparation technology and adopts a co-deposition method to load elemental sulfur and elemental silicon onto the graphene surface. Through the synergistic effect of the three, a graphene / sulfur / silicon multi-composite material for making battery electrodes is obtained, which exhibits good energy storage performance, cycle performance and rate performance.

[0004] To achieve the above object, the present invention adopts the following technical solutions:

[0005] In a first aspect, the present invention provides a graphene / sulfur / silicon multi-composite material for making battery electrodes, which is a multi-composite material with graphene as a substrate loaded with nano-sulfur and nano-silicon; in the multi-composite material, nano-silicon is deposited on the surface of graphene, and nano-sulfur is uniformly crystallized on the surface of nano-silicon particles and between the particles.

[0006] In a second aspect, the present invention provides a method for preparing the above-mentioned graphene / sulfur / silicon multi-composite material, comprising the following steps: S1, dispersing graphene in a solvent to obtain a solution A; dissolving nano-sulfur in the solvent to obtain a solution B; and uniformly mixing the solution A, the solution B and the nano-silicon to obtain a mixed solution C;

[0007] S2, leaving the mixed solution C to stand, waiting for elemental sulfur to precipitate out of the solution and crystallize on the graphene surface, slowly adding ionized water to separate the solvent mixed solution and the water layer; since the density of the solvent mixed solution is relatively small compared to the density of water, the upper layer is the solvent and the lower layer is water; removing the solvent in the upper layer to obtain a powder-water mixed solution;

[0008] S3, drying the powder-water mixture, and heating it under an inert atmosphere to obtain the graphene / sulfur / silicon multi-component composite material.

[0009] Furthermore, in S1, the solvent is one or more of toluene, carbon disulfide, carbon tetrachloride, and cyclohexane.

[0010] Furthermore, in S1, the solvent in the solution A is toluene, and the mass concentration of solution A is 5-15wt%, preferably 10wt%; the solvent in the solution B is a mixed solvent of carbon disulfide and toluene, and the mass ratio of carbon disulfide to toluene in the mixed solvent is 1:2-10; in the mixed solution C, the mass ratio of graphene to nano-sulfur is 1:10-1000, and the mass of nano-silicon accounts for 1-90% of the total mass of graphene, nano-sulfur and nano-silicon.

[0011] Further, in S1, the graphene is reduced graphene oxide prepared by a redox method using graphite powder as a raw material, and the preparation method comprises the following steps:

[0012] Hummers preparation of graphite oxide: 58 ml of 98% concentrated sulfuric acid is placed in an ice water bath, and when the temperature drops to 0-5°C, slowly stir, and uniformly add 2.5 g of graphite powder, 7.5 g of potassium permanganate and 1.25 g of sodium nitrate in sequence, and stir at a low temperature of 200 r / min for 2 hours; 115 ml of deionized water is slowly added at a rate of 1-2 drops / s, and the temperature is raised to 95°C. After the temperature stabilizes, 150 ml of deionized water is uniformly added, and the temperature is lowered to 30-40°C, and then 30 wt% of hydrogen peroxide is added to remove excess potassium permanganate, and then washed with deionized water until neutral, and dried at 80°C to obtain graphite oxide powder;

[0013] Preparation of reduced graphene oxide by high-temperature expansion reduction: the graphite oxide powder is expanded at 800° C. for 30 seconds under an inert atmosphere, and then reduced at 800° C. for 1 hour under an inert atmosphere to obtain reduced graphene oxide.

[0014] Furthermore, in S1, the temperature at which nano-sulfur is dissolved in the solvent is 25-80°C; in S2, the temperature at which elemental sulfur is precipitated and crystallized from the mixed solution C is 0-5°C. The solubility of nano-sulfur in the solvent increases with increasing temperature, and the effect is most obvious in toluene. Conversely, as the temperature decreases, the solubility decreases, and the low temperature environment causes sulfur to precipitate from the solvent and deposit on the graphene surface; in S3, the heating temperature is 150-300°C, and the time is 1h.

[0015] In a third aspect, the present invention provides a battery, wherein the negative electrode material comprises the above-mentioned graphene / sulfur / silicon multi-composite material.

[0016] Furthermore, the battery is a lithium-ion battery; the negative electrode material includes graphite and the graphene / sulfur / silicon multi-composite material; during the preparation of the graphene / sulfur / silicon multi-composite material, the mass ratio of nano-sulfur to nano-silicon is 1:1-10, and nano-silicon accounts for 50-90% of the total mass of graphene, nano-sulfur and nano-silicon; the graphene / sulfur / silicon multi-composite material accounts for 0.1-90% of the sum of the mass of graphite and the graphene / sulfur / silicon multi-composite material.

[0017] Furthermore, during the preparation of the graphene / sulfur / silicon multi-composite material, the mass ratio of nano-sulfur to nano-silicon is 1:2-3, and nano-silicon accounts for 67-75% of the total mass of graphene, nano-sulfur and nano-silicon.

[0018] The preparation method of the lithium-ion battery is as follows: graphite, graphene / sulfur / silicon multi-composite material, sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) are mixed into slurry by deionized water; the graphite and graphene / sulfur / silicon multi-composite material account for 90-99% of the total mass of all powders; the slurry is evenly coated on the surface of the copper foil, and the moisture is removed by high-temperature baking to obtain a pole piece; the pole piece is rolled according to a certain compaction ratio to obtain an electrode; the electrode is used as a negative electrode material of the lithium-ion battery, and a lithium metal sheet is used as a positive electrode material to assemble the lithium-ion battery.

[0019] Furthermore, the battery is a lithium-sulfur battery; the positive electrode material includes graphite and the graphene / sulfur / silicon multi-composite material; during the preparation of the graphene / sulfur / silicon multi-composite material, the mass ratio of nano-sulfur to nano-silicon is 1 to 100:1; the graphene / sulfur / silicon multi-composite material accounts for 90 to 100% of the sum of the mass of graphite and the graphene / sulfur / silicon multi-composite material.

[0020] The preparation method of the lithium-sulfur battery is as follows: graphite, graphene / sulfur / silicon multi-composite material, sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) are mixed into slurry by deionized water; graphite and graphene / sulfur / silicon multi-composite material account for 90-99% of the total mass of all powders; the slurry is evenly coated on the surface of aluminum foil, and moisture is removed by high-temperature baking to obtain a pole piece; the pole piece is rolled according to a certain compaction ratio to obtain an electrode; the electrode is used as a positive electrode material of the lithium-sulfur battery, and a lithium metal sheet is used as a negative electrode material to assemble a lithium-sulfur battery.

[0021] The present invention utilizes graphene with high conductivity and large specific surface area and nano-sulfur and nano-silicon co-deposition method to prepare electrode materials with high discharge specific capacity and good cycle stability. Elemental silicon is deposited on the surface of graphene by a simple liquid phase co-deposition method, elemental sulfur is precipitated from the solution by low temperature treatment and uniformly crystallized on the surface of silicon particles and between particles, and the excellent conductivity of graphene is utilized. During the battery charging and discharging process, lithium ions are combined with elemental silicon and elemental sulfur to form silicide and sulfide, but due to the different melting points of sulfur (melting point 113° C.) and silicon (melting point 1414° C.), sulfur and silicon have different expansion rates after lithium insertion, the former has a small expansion (<80%), and the latter has a large expansion (expansion rate of nearly 300%), and the sulfur with a small expansion forms a structural skeleton between the gaps of silicon particles, which is equivalent to increasing the binding force on the silicon particles and filling the pores between the silicon particles. The two materials restrain each other to reduce the expansion between the particles, and can be used as an active material to provide lithium insertion opportunities for lithium ions, and is applied to batteries by regulating the sulfur-silicon ratio and the ratio of the composite material to the active material.

[0022] The beneficial effects of the present invention are:

[0023] The present invention utilizes the relationship between the solubility and temperature of elemental sulfur in toluene / carbon disulfide solvent, dissolves in a high temperature environment, and crystallizes on the surface of graphene and silicon powder in a low temperature environment, thereby obtaining a graphene / sulfur / silicon multi-component composite material for making battery electrodes. Sulfur and silicon are physically mixed by utilizing different melting points and different expansion rates after lithium insertion. After melting, sulfur is coated on the surface of part of the silicon particles and between the particles. The expansion of sulfur is small, and it plays a role similar to a structural skeleton between silicon particles, directly physically inhibiting the expansion of silicon. By controlling the ratio of sulfur to silicon, it can be used as a negative electrode active main material or active material additive in polymer lithium-ion batteries, and can also be used as a positive electrode active main material in lithium-sulfur batteries.

[0024] In particular, in lithium-ion batteries, adding silicon can effectively increase the actual specific capacity of the battery, but it is also easy to cause expansion problems. The present invention uses a graphene / sulfur / silicon multi-composite material to effectively avoid the silicon expansion problem. Specifically, after heat treatment, sulfur melts to the surface of silicon particles, adding a partial "sulfur coating" to the surface of the silicon particles, which is equivalent to Li +When silicon particles are intercalated and deintercalated, a protective barrier is added to inhibit the expansion of silicon particles, thereby reducing irreversible damage to the particles. In addition, sulfur in the same family also has the ability to intercalate lithium, and the synergistic effect increases the chance of lithium ion insertion to achieve the effect of improving reversible capacity and energy density.

[0025] In addition, in the preparation of graphene / sulfur / silicon multi-composite materials, after elemental sulfur is precipitated and crystallized at low temperature, deionized water is injected to separate the solvent in the mixed liquid. The separated solvent can be reused, which greatly reduces the production cost and is conducive to industrial production.

[0026] The present invention utilizes the advantages of each component material through material composite technology to overcome the defects of a single material, and the prepared graphene / sulfur / silicon multi-composite material has the advantages of high charge and discharge capacity, long cycle life and good rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a rate discharge cycle curve diagram of the lithium ion batteries of Examples 1 to 5;

[0028] Figure 2 It is a bar graph of the thickness of the negative electrode sheet of the lithium-ion button cells of Examples 1 to 5 and the lithium-ion button cells containing the graphene / silicon composite material before and after charging and discharging. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments.

[0030] Example 1

[0031] This embodiment provides a lithium-ion battery, wherein the negative electrode material includes a graphene / sulfur / silicon multi-composite material.

[0032] The preparation method of the graphene / sulfur / silicon multi-component composite material comprises the following steps:

[0033] S1. Dispersing graphene in toluene to obtain a solution A with a mass concentration of 10 wt%.

[0034] Carbon disulfide and toluene are mixed in a mass ratio of 1:2 to prepare a mixed solvent; nano-sulfur is dissolved in the mixed solvent at an ambient temperature of 25° C. to obtain a solution B.

[0035] Solution A and solution B are mixed and nano-silicon is added, and the mixture is stirred evenly to obtain a mixed solution C. The mixed solution C contains 0.1 g of graphene, 50 g of nano-sulfur and 450 g of nano-silicon. That is, the mass ratio of graphene to nano-sulfur is 1:500, the mass ratio of nano-sulfur to nano-silicon is 1:9, and the mass of nano-silicon accounts for 90% of the total mass of graphene, nano-sulfur and nano-silicon.

[0036] S2. Ultrasonic disperse the mixed solution C for 20 minutes, transfer it to a 0-5℃ environment and let it stand for a while. After the nano-sulfur precipitates from the solution, slowly add deionized water near the wall of the beaker to separate the toluene mixed solution and the water. Remove the upper layer of toluene mixed solution to leave the powder-water mixed solution.

[0037] S3, the powder-water mixture is filtered and dried in a vacuum drying oven at 60°C for 12 hours. The dried powder is heated in a tube furnace at 150°C for 1 hour under the protection of an inert gas such as argon to obtain a graphene / sulfur / silicon multi-component composite material.

[0038] The preparation method of the lithium-ion battery is as follows: graphite and graphene / sulfur / silicon multi-composite materials are mixed with sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 97.5:1.0:1.5 by deionized water to form a slurry. Among them, the graphene / sulfur / silicon multi-composite material accounts for 10% of the sum of the mass of graphite and graphene / sulfur / silicon multi-composite materials; graphite and graphene / sulfur / silicon multi-composite materials account for 97.5% of the total mass of all powders. The slurry is evenly coated on the surface of the copper foil, and the water is removed by high-temperature baking to obtain a pole piece; the pole piece is rolled according to a certain compaction ratio to obtain an electrode; the electrode is used as the negative electrode material of the lithium-ion battery, and the lithium metal sheet is used as the positive electrode material to assemble into a lithium-ion button battery.

[0039] Example 2

[0040] This embodiment provides a lithium-ion battery, wherein the negative electrode material includes a graphene / sulfur / silicon multi-composite material.

[0041] The preparation method of the graphene / sulfur / silicon multi-component composite material comprises the following steps:

[0042] S1. Dispersing graphene in toluene to obtain a solution A with a mass concentration of 10 wt%.

[0043] Carbon disulfide and toluene are mixed in a mass ratio of 1:2 to prepare a mixed solvent; nano-sulfur is dissolved in the mixed solvent at an ambient temperature of 45° C. to obtain solution B.

[0044] Solution A and solution B are mixed and nano-silicon is added, and the mixture is stirred evenly to obtain a mixed solution C. The mixed solution C contains 0.1 g of graphene, 50 g of nano-sulfur and 150 g of nano-silicon. That is, the mass ratio of graphene to nano-sulfur is 1:500, the mass ratio of nano-sulfur to nano-silicon is 1:3, and the mass of nano-silicon accounts for 75% of the total mass of graphene, nano-sulfur and nano-silicon.

[0045] S2. Ultrasonic disperse the mixed solution C for 20 minutes, transfer it to a 0-5℃ environment and let it stand for a while. After the nano-sulfur precipitates from the solution, slowly add deionized water near the wall of the beaker to separate the toluene mixed solution and the water. Remove the upper layer of toluene mixed solution to leave the powder-water mixed solution.

[0046] S3, the powder-water mixture is filtered and dried in a vacuum drying oven at 60°C for 12 hours. The dried powder is heated in a tube furnace at 150°C for 1 hour under the protection of an inert gas such as argon to obtain a graphene / sulfur / silicon multi-component composite material.

[0047] The preparation method of the lithium-ion battery is as follows: graphite and graphene / sulfur / silicon multi-composite materials are mixed with sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 97.5:1.0:1.5 by deionized water to form a slurry. Among them, the graphene / sulfur / silicon multi-composite material accounts for 10% of the sum of the mass of graphite and graphene / sulfur / silicon multi-composite materials; graphite and graphene / sulfur / silicon multi-composite materials account for 97.5% of the total mass of all powders. The slurry is evenly coated on the surface of the copper foil, and the water is removed by high-temperature baking to obtain a pole piece; the pole piece is rolled according to a certain compaction ratio to obtain an electrode; the electrode is used as the negative electrode material of the lithium-ion battery, and the lithium metal sheet is used as the positive electrode material to assemble into a lithium-ion button battery.

[0048] Example 3

[0049] This embodiment provides a lithium-ion battery, wherein the negative electrode material includes a graphene / sulfur / silicon multi-composite material.

[0050] The preparation method of the graphene / sulfur / silicon multi-component composite material comprises the following steps:

[0051] S1. Dispersing graphene in toluene to obtain a solution A with a mass concentration of 10 wt%.

[0052] Carbon disulfide and toluene are mixed in a mass ratio of 1:2 to prepare a mixed solvent; nano-sulfur is dissolved in the mixed solvent at an ambient temperature of 45° C. to obtain solution B.

[0053] Solution A and solution B are mixed and nano-silicon is added, and the mixture is stirred evenly to obtain a mixed solution C. The mixed solution C contains 0.1 g of graphene, 50 g of nano-sulfur, and 100 g of nano-silicon. That is, the mass ratio of graphene to nano-sulfur is 1:500, the mass ratio of nano-sulfur to nano-silicon is 1:2, and the mass of nano-silicon accounts for 67% of the total mass of graphene, nano-sulfur, and nano-silicon.

[0054] S2. Ultrasonic disperse the mixed solution C for 20 minutes, transfer it to a 0-5℃ environment and let it stand for a while. After the nano-sulfur precipitates from the solution, slowly add deionized water near the wall of the beaker to separate the toluene mixed solution and the water. Remove the upper layer of toluene mixed solution to leave the powder-water mixed solution.

[0055] S3, the powder-water mixture is filtered and dried in a vacuum drying oven at 60°C for 12 hours. The dried powder is heated in a tube furnace at 150°C for 1 hour under the protection of an inert gas such as argon to obtain a graphene / sulfur / silicon multi-component composite material.

[0056] The preparation method of the lithium-ion battery is as follows: graphite and graphene / sulfur / silicon multi-composite materials are mixed with sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 97.5:1.0:1.5 by deionized water to form a slurry. Among them, the graphene / sulfur / silicon multi-composite material accounts for 10% of the sum of the mass of graphite and graphene / sulfur / silicon multi-composite materials; graphite and graphene / sulfur / silicon multi-composite materials account for 97.5% of the total mass of all powders. The slurry is evenly coated on the surface of the copper foil, and the water is removed by high-temperature baking to obtain a pole piece; the pole piece is rolled according to a certain compaction ratio to obtain an electrode; the electrode is used as the negative electrode material of the lithium-ion battery, and the lithium metal sheet is used as the positive electrode material to assemble into a lithium-ion button battery.

[0057] Example 4

[0058] This embodiment provides a lithium-ion battery, wherein the negative electrode material includes a graphene / sulfur / silicon multi-composite material.

[0059] The preparation method of the graphene / sulfur / silicon multi-component composite material comprises the following steps:

[0060] S1. Dispersing graphene in toluene to obtain a solution A with a mass concentration of 10 wt%.

[0061] Carbon disulfide and toluene are mixed in a mass ratio of 1:2 to prepare a mixed solvent; nano-sulfur is dissolved in the mixed solvent at an ambient temperature of 45° C. to obtain solution B.

[0062] Solution A and solution B are mixed and nano-silicon is added, and the mixture is stirred evenly to obtain a mixed solution C. The mixed solution C contains 0.1 g of graphene, 50 g of nano-sulfur and 50 g of nano-silicon. That is, the mass ratio of graphene to nano-sulfur is 1:500, the mass ratio of nano-sulfur to nano-silicon is 1:1, and the mass of nano-silicon accounts for 50% of the total mass of graphene, nano-sulfur and nano-silicon.

[0063] S2. Ultrasonic disperse the mixed solution C for 20 minutes, transfer it to a 0-5℃ environment and let it stand for a while. After the nano-sulfur precipitates from the solution, slowly add deionized water near the wall of the beaker to separate the toluene mixed solution and the water. Remove the upper layer of toluene mixed solution to leave the powder-water mixed solution.

[0064] S3, the powder-water mixture is filtered and dried in a vacuum drying oven at 60°C for 12 hours. The dried powder is heated in a tube furnace at 150°C for 1 hour under the protection of an inert gas such as argon to obtain a graphene / sulfur / silicon multi-component composite material.

[0065] The preparation method of the lithium-ion battery is as follows: graphite and graphene / sulfur / silicon multi-composite materials are mixed with sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 97.5:1.0:1.5 by deionized water to form a slurry. Among them, the graphene / sulfur / silicon multi-composite material accounts for 10% of the sum of the mass of graphite and graphene / sulfur / silicon multi-composite materials; graphite and graphene / sulfur / silicon multi-composite materials account for 97.5% of the total mass of all powders. The slurry is evenly coated on the surface of the copper foil, and the water is removed by high-temperature baking to obtain a pole piece; the pole piece is rolled according to a certain compaction ratio to obtain an electrode; the electrode is used as the negative electrode material of the lithium-ion battery, and the lithium metal sheet is used as the positive electrode material to assemble into a lithium-ion button battery.

[0066] Example 5

[0067] This embodiment provides a lithium-ion battery, wherein the negative electrode material includes a graphene / sulfur / silicon multi-composite material.

[0068] The preparation method of the graphene / sulfur / silicon multi-component composite material comprises the following steps:

[0069] S1. Dispersing graphene in toluene to obtain a solution A with a mass concentration of 10 wt%.

[0070] Carbon disulfide and toluene are mixed in a mass ratio of 1:2 to prepare a mixed solvent; nano-sulfur is dissolved in the mixed solvent at an ambient temperature of 45° C. to obtain solution B.

[0071] Solution A and solution B are mixed and nano-silicon is added, and the mixture is stirred evenly to obtain a mixed solution C. The mixed solution C contains 5 g of graphene, 50 g of nano-sulfur and 495 g of nano-silicon. That is, the mass ratio of graphene to nano-sulfur is 1:500, the mass ratio of nano-sulfur to nano-silicon is 1:10, and the mass of nano-silicon accounts for 90% of the total mass of graphene, nano-sulfur and nano-silicon.

[0072] S2. Ultrasonic disperse the mixed solution C for 20 minutes, transfer it to a 0-5℃ environment and let it stand for a while. After the nano-sulfur precipitates from the solution, slowly add deionized water near the wall of the beaker to separate the toluene mixed solution and the water. Remove the upper layer of toluene mixed solution to leave the powder-water mixed solution.

[0073] S3, the powder-water mixture is filtered and dried in a vacuum drying oven at 60°C for 12 hours. The dried powder is heated in a tube furnace at 150°C for 1 hour under the protection of an inert gas such as argon to obtain a graphene / sulfur / silicon multi-component composite material.

[0074] The preparation method of the lithium-ion battery is as follows: graphite and graphene / sulfur / silicon multi-composite materials are mixed with sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 97.5:1.0:1.5 by deionized water to form a slurry. Among them, the graphene / sulfur / silicon multi-composite material accounts for 10% of the sum of the mass of graphite and graphene / sulfur / silicon multi-composite materials; graphite and graphene / sulfur / silicon multi-composite materials account for 97.5% of the total mass of all powders. The slurry is evenly coated on the surface of the copper foil, and the water is removed by high-temperature baking to obtain a pole piece; the pole piece is rolled according to a certain compaction ratio to obtain an electrode; the electrode is used as the negative electrode material of the lithium-ion battery, and the lithium metal sheet is used as the positive electrode material to assemble into a lithium-ion button battery.

[0075] The cell performance of the lithium ion button cells prepared in Examples 1 to 5 was tested, and the rate discharge cycle curves thereof were as follows: Figure 1 shown.

[0076] The thickness of the negative electrode sheet of the lithium ion button cells prepared in Examples 1 to 5 and the lithium ion button cells containing the graphene / silicon composite material before and after charging and discharging was compared. Figure 2 The preparation method of the lithium ion button cell containing the graphene / silicon composite material is basically the same as that in Example 1, except that sulfur is not added to the graphene / silicon composite material. Figure 2 It can be seen that compared with the battery whose negative electrode contains only silicon, the expansion rate of the negative electrode plate is greatly reduced after composite sulfur.

[0077] comprehensive Figure 1 and Figure 2 It can be seen that when the mass ratio of nanosulfur to nanosilicon is 1:2-3, and nanosilicon accounts for 67-75% of the total mass of graphene, nanosulfur and nanosilicon, the lithium-ion button battery can achieve good practical specific capacity while having a small expansion rate.

[0078] Example 6

[0079] This embodiment provides a lithium-sulfur battery, wherein the positive electrode material includes a graphene / sulfur / silicon multi-composite material.

[0080] The preparation method of the graphene / sulfur / silicon multi-component composite material comprises the following steps:

[0081] S1. Dispersing graphene in toluene to obtain a solution A with a mass concentration of 10 wt%.

[0082] Carbon disulfide and toluene are mixed in a mass ratio of 1:2 to prepare a mixed solvent; nano-sulfur is dissolved in the mixed solvent at an ambient temperature of 65° C. to obtain a solution B.

[0083] Solution A and solution B are mixed and nano-silicon is added, and the mixture is stirred evenly to obtain a mixed solution C, wherein the mass ratio of graphene to nano-sulfur is 0.5:50, the mass ratio of nano-sulfur to nano-silicon is 50:5, and the mass of nano-silicon accounts for 9% of the total mass of graphene, nano-sulfur and nano-silicon.

[0084] S2. Ultrasonic disperse the mixed solution C for 20 minutes, transfer it to a 0-5℃ environment and let it stand for a while. After the nano-sulfur precipitates from the solution, slowly add deionized water near the wall of the beaker to separate the toluene mixed solution and the water. Remove the upper layer of toluene mixed solution to leave the powder-water mixed solution.

[0085] S3, the powder-water mixture is filtered and dried in a vacuum drying oven at 60°C for 12 hours. The dried powder is heated in a tube furnace at 150°C for 1 hour under the protection of an inert gas such as argon to obtain a graphene / sulfur / silicon multi-component composite material.

[0086] The preparation method of the lithium-sulfur battery is as follows: graphite and graphene / sulfur / silicon multi-composite materials are mixed with sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 98:1.0:1.0 by deionized water to form a slurry. Among them, the graphene / sulfur / silicon multi-composite material accounts for 95% of the sum of the mass of graphite and graphene / sulfur / silicon multi-composite materials; graphite and graphene / sulfur / silicon multi-composite materials account for 98% of the total mass of all powders. The slurry is evenly coated on the surface of the aluminum foil, and the water is removed by high-temperature baking to obtain a pole piece; the pole piece is rolled according to a certain compaction ratio to obtain an electrode; the electrode is used as the positive electrode material of the lithium-sulfur battery, and the lithium metal sheet is used as the negative electrode material to assemble the lithium-sulfur battery.

[0087] Example 7

[0088] This embodiment provides a lithium-sulfur battery, wherein the positive electrode material includes a graphene / sulfur / silicon multi-composite material.

[0089] The preparation method of the graphene / sulfur / silicon multi-component composite material comprises the following steps:

[0090] S1. Dispersing graphene in toluene to obtain a solution A with a mass concentration of 10 wt%.

[0091] Carbon disulfide and toluene are mixed in a mass ratio of 1:2 to prepare a mixed solvent; nano-sulfur is dissolved in the mixed solvent at an ambient temperature of 85° C. to obtain a solution B.

[0092] Solution A and solution B are mixed and nano-silicon is added, and the mixture is stirred evenly to obtain a mixed solution C. The mass ratio of graphene to nano-sulfur is 0.5:245, the mass ratio of nano-sulfur to nano-silicon is 245:5, and the mass of nano-silicon accounts for 2% of the total mass of graphene, nano-sulfur and nano-silicon.

[0093] S2. Ultrasonic disperse the mixed solution C for 20 minutes, transfer it to a 0-5℃ environment and let it stand for a while. After the nano-sulfur precipitates from the solution, slowly add deionized water near the wall of the beaker to separate the toluene mixed solution and the water. Remove the upper layer of toluene mixed solution to leave the powder-water mixed solution.

[0094] S3, the powder-water mixture is filtered and dried in a vacuum drying oven at 60°C for 12 hours. The dried powder is heated in a tube furnace at 150°C for 1 hour under the protection of an inert gas such as argon to obtain a graphene / sulfur / silicon multi-component composite material.

[0095] The preparation method of the lithium-sulfur battery is as follows: graphite and graphene / sulfur / silicon multi-composite materials are mixed with sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 98:1.0:1.0 by deionized water to form a slurry. Among them, the graphene / sulfur / silicon multi-composite material accounts for 95% of the sum of the mass of graphite and graphene / sulfur / silicon multi-composite materials; graphite and graphene / sulfur / silicon multi-composite materials account for 98% of the total mass of all powders. The slurry is evenly coated on the surface of the aluminum foil, and the water is removed by high-temperature baking to obtain a pole piece; the pole piece is rolled according to a certain compaction ratio to obtain an electrode; the electrode is used as the positive electrode material of the lithium-sulfur battery, and the lithium metal sheet is used as the negative electrode material to assemble the lithium-sulfur battery.

[0096] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields.

[0097] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A graphene / sulfur / silicon multi-component composite material for making battery electrodes, characterized in that: It is a multi-composite material with graphene as the substrate and loaded with nano-sulfur and nano-silicon; in the multi-composite material, nano-silicon is deposited on the surface of graphene, and nano-sulfur is uniformly crystallized on the surface of nano-silicon particles and between the particles.

2. The method for preparing the graphene / sulfur / silicon multi-component composite material according to claim 1, characterized in that: The following steps are involved: S1, dispersing graphene in a solvent to obtain a solution A; Dissolving nanosulfur in a solvent to obtain solution B; Mix solution A, solution B and nano-silicon evenly to obtain a mixed solution C; S2, allowing the mixed solution C to stand, waiting for elemental sulfur to precipitate out of the solution and crystallize on the graphene surface, slowly adding deionized water to separate the solvent and water; removing the solvent in the upper layer to obtain a powder-water mixed solution; S3, drying the powder-water mixture, and then heat-treating it to obtain the graphene / sulfur / silicon multi-component composite material.

3. The method for preparing the graphene / sulfur / silicon multi-component composite material according to claim 2, characterized in that: In S1, the solvent is one or more of toluene, carbon disulfide, carbon tetrachloride, and cyclohexane.

4. The method for preparing the graphene / sulfur / silicon multi-component composite material according to claim 3, characterized in that: In S1, the solvent in the solution A is toluene, and the mass concentration of the solution A is 5-15wt%; The solvent in the solution B is a mixed solvent of carbon disulfide and toluene, and the mass ratio of carbon disulfide to toluene in the mixed solvent is 1:2-10; In the mixed solution C, the mass ratio of graphene to nano-sulfur is 1:10-1000, and nano-silicon accounts for 1-90% of the total mass of graphene, nano-sulfur and nano-silicon.

5. The method for preparing the graphene / sulfur / silicon multi-component composite material according to claim 2, characterized in that: In S1, the graphene is reduced graphene oxide prepared by a redox method using graphite powder as a raw material.

6. The method for preparing the graphene / sulfur / silicon multi-component composite material according to claim 2, characterized in that: In S1, the temperature at which nanosulfur is dissolved in the solvent is 25 to 80°C; In S2, the temperature at which elemental sulfur precipitates and crystallizes from the mixed solution C is 0 to 5°C; In S3, the heat treatment method is: heating at 150-300° C. for 1 hour under an inert atmosphere.

7. A battery, characterized in that: It includes the graphene / sulfur / silicon multi-composite material as claimed in claim 1.

8. The battery according to claim 7, characterized in that: The battery is a lithium-ion battery; the negative electrode material includes graphite and the graphene / sulfur / silicon multi-component composite material; During the preparation of the graphene / sulfur / silicon multi-composite material, the mass ratio of nano-sulfur to nano-silicon is 1:1-10, nano-silicon accounts for 50-90% of the total mass of graphene, nano-sulfur and nano-silicon; and the graphene / sulfur / silicon multi-composite material accounts for 0.1-90% of the sum of the mass of graphite and the graphene / sulfur / silicon multi-composite material.

9. The battery according to claim 8, characterized in that: During the preparation of the graphene / sulfur / silicon multi-component composite material, the mass ratio of nano-sulfur to nano-silicon is 1:2-3, and nano-silicon accounts for 67-75% of the total mass of graphene, nano-sulfur and nano-silicon.

10. The battery according to claim 7, characterized in that: The battery is a lithium-sulfur battery; the positive electrode material includes graphite and the graphene / sulfur / silicon multi-component composite material; During the preparation of the graphene / sulfur / silicon multi-composite material, the mass ratio of nano-sulfur to nano-silicon is 1-100:1; the graphene / sulfur / silicon multi-composite material accounts for 90-100% of the sum of the mass of graphite and the graphene / sulfur / silicon multi-composite material.